Crystallization behavior of BaO–CaO–SiO2–B2O3 glass sealant and adjusting its thermal properties for oxygen transport membrane joining application. Issue 6 (June 2023) - Li, Xinfang; Yazhenskikh, Elena; Groß-Barsnick, Sonja M.; Baumann, Stefan; Behr, Patrick; Deibert, Wendelin; Koppitz, Thomas; Müller, Michael; Meulenberg, Wilhelm A.; Natour, Ghaleb
Abstract: In this work, the thermal stability of a BaO–CaO–SiO2 –B2 O3 glass sealant, named "H", was investigated by differential scanning calorimetry (DSC). The crystallization behavior of glass H as the sealant matrix was investigated by a combination of experimental X-ray diffraction (XRD) analysis and thermodynamic simulation with the FactSage package. A good agreement was found between the Rietveld refinement of XRD experiments and the FactSage simulation. Particular attention was also given to the influence of the Sr2 SiO4 filler added to the glass matrix "H" on the thermal expansion and microstructures of glass-Sr2 SiO4 composites by means of dilatometry and scanning electron microscopy (SEM). The reinforced 20 wt% Sr2 SiO4 composite (HS2S20) showed excellent properties and, thus, its joining performance was investigated using SrTi0.75 Fe0.25 O3-δ (STF25) and Aluchrom as promising oxygen transport membrane (OTM) and counterpart, respectively. The joining behaviors were investigated by comparing different joining temperatures. 920 °C is the best joining temperature for HS2S20 sealant.